A cohort study comparing 4 mg and 10 mg daily doses of postoperative oestradiol therapy to prevent adhesion reformation after hysteroscopic adhesiolysis. (3rd July 2019) - Liu, Linlin; Huang, Xiaowu; Xia, Enlan; Zhang, Xiaoyu; Li, Tin-Chiu; Liu, Yuhuan
Abstract: This is a retrospective cohort study conducted in a national training centre for hysteroscopy between January 2012 and December 2014 to compare the clinical outcome of two doses of oestradiol valerate (4 mg and 10 mg daily) in the prevention of recurrence of adhesions after hysteroscopic adhesiolysis. A total of 176 women who suffered from Asherman syndrome with moderate to severe intrauterine adhesions were included: 91 subjects received a 10 mg daily dose of oestradiol and 85 subjects received a 4 mg daily dose of oestradiol in the postoperative period. Second look hysteroscopy was performed 4–6 weeks after the initial surgery. There was no difference in age and preoperative American Fertility Society (AFS) adhesion score between the two groups. The proportion of women in whom menstruation had returned to normal in the 10 mg group (49/91 = 53.8%) was significantly ( p  < 0.05) higher than that of subjects in the 4 mg group (35/85 = 41.2%). However, there was no difference in AFS scores at second look hysteroscopy between the two groups or in the conception rate and miscarriage rate between the two groups. The findings do not support the use of high-dose postoperative oestrogen therapy following hysteroscopic adhesiolysis.